2017
DOI: 10.1109/tase.2017.2648789
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Distributed Control of Biogas Supply and Multienergy Demand

Abstract: In this paper we study the coordination between biogas producers who can either use the biogas themselves, exchange biogas with their neighbors, or deliver it to the various energy grids, such as the low pressure gas grid or the power grid. These producers are called prosumers. In this setting gas storage, fuel cells, micro combined heat power systems, and heat buffers are all part of the prosumers' node. We aim to optimize the imbalance, profit, and comfort levels per prosumer, while taking the constraints of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
(77 reference statements)
0
12
0
Order By: Relevance
“…Moreover, we show that the asynchronous algorithm converges in O(1/k), which, to the best of our knowledge, has not been presented in the existing literature [6], [15]- [19].…”
Section: Convergence Analysismentioning
confidence: 58%
See 2 more Smart Citations
“…Moreover, we show that the asynchronous algorithm converges in O(1/k), which, to the best of our knowledge, has not been presented in the existing literature [6], [15]- [19].…”
Section: Convergence Analysismentioning
confidence: 58%
“…By simply setting the inexactness or asynchrony parameter as zero, our result reduces to that given in [16] or [21], respectively. Our work also first gives the O(1/k) convergence rate for the asynchronous DD-DO algorithm, which, to the best of our knowledge, has not been presented in the existing literature [6], [16]- [18].…”
Section: Contributionsmentioning
confidence: 92%
See 1 more Smart Citation
“…At the level of the prosumers, the minimization of the prediction error in the operate phase is solved in a distributed manner, where each prosumer contributes to the optimization process based only on local information exchange with their neighbors. In [19], which considers a similar distributed MPC framework, although not in a market-based structure, it has been shown that the more information the prosumers share with each other, the less imbalance there is in the network. The role of the DSO is included in the model to avoid violation of the distribution network capacities.…”
Section: Tso and Brp (1-to-n) 15mentioning
confidence: 99%
“…In practice, the communication channel is never perfect noting time delay, packet drops, congestion, and even failures [11]- [13]. In addition, nonidentical sampling/computation rates of different MGs also exist [14]. Then, asynchrony arises, which has a detrimental impact on the controller response speed, MG stability, and optimal operation [15]- [17].…”
mentioning
confidence: 99%